The five year experience of work in social care department of Šiauliai institution. - Brijūnaitė, Rita (Socialinė teorija, empirija, politika ir praktika, 2003)
The history and experience of social care department in institution is presented in the paper. It is a fact, that the beginning of social work is parallel to the independence of Lithuania, in spite of this the social work in the institution was organised during the communist period. The first social care department in institution was established in the institution in 1996. It was the first establishment of the department in Lithuania. The informative support and practical help were at the core of the department’s activity in the beginning. Later, the organisation of psychosocial rehabilitation was initiated by social workers. The development of social care was led by the occurrence of problems and they are discussed as well.